Microplastic contamination in the Skipjack Tuna (Euthynnus affinis) collected from Southern Coast of Java, Indonesia. (August 2021) - Andreas; Hadibarata, Tony; Sathishkumar, Palanivel; Prasetia, Hafiizh; Hikmat; Pusfitasari, Eka Dian; Tasfiyati, Aprilia Nur; Muzdalifah, Dian; Waluyo, Joko; Randy, Ahmad; Ramadhaningtyas, Dillani Putri; Zuas, Oman; et al.
Abstract: Indonesia is the second-largest contributor of microplastics (MPs) pollution in the marine ecosystem. Most MPs pollution-related studies in Indonesia focus on seawater, sediment, with less information found on the commercially important fish species used for human consumption. Skipjack Tuna (Euthynnus affinis) is one of the major exporting fishery commodities from Indonesia. This exploratory study aimed to determine MPs presence in the digestive tract of Skipjack Tuna from the Southern Coast of Java, Indonesia. The fish samples were collected from five different fish traditional auction market along the Southern Coast of Java, Indonesia, namely Pangandaran, Pamayang Sari, Ciletuh, Santolo, and Palabuhan Ratu. The gastrointestinal tract of Skipjack tuna was pretreated using alkaline destruction and filtered. The presence of MPs in the treated samples was visually identified using an optical microscope, while Polybrominated diphenyl ethers (PBDEs) contaminants were analyzed using Gas Chromatography-Mass Spectrometry (GC-MS). A total of 19 suspected MPs particles were found in the form of filament (84%), angular (11%), and round (5%). This result would provide a better indication of the MPs contamination in marine life species in the Southern Coast of Java, Indonesia, as useful information for marine environmental monitoring program in the future. Graphical abstract: Image 1 Highlights: MPs were found in the Skipjack tuna from the Southern Coast of Java, Indonesia. MPs were found in the form of filament (84%), angular (11%), and round (5%). The size of the detected MPs was found between 0.25 and 5 mm. PBDEs is a potential marker for the detection of microplastic contamination in fish.